2010
DOI: 10.1038/ajh.2010.16
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of the Elastin Microfibril Interfacer 1 (EMILIN1) Gene in Essential Hypertension

Abstract: We confirmed that rs2289360, rs2011616, and rs2304682 in the human EMILIN1 gene, as well as the haplotype constructed using rs2536512, rs2011616, and rs17881426 are useful genetic markers of EH in Japanese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…Cry1/2 −/− mice show elevated transcription and enhanced enzymatic activity of type VI 3β-hydroxyl-steroid dehydrogenase (Hsd3b6), which is expressed exclusively in aldosterone-producing cells under transcriptional control of the circadian clock. Moreover, single-nucleotide polymorphisms in the HSD3B1 gene, the human ortholog of Hsd3b6, are associated with elevated systolic and diastolic blood pressure and plasma aldosterone activity (Rosmond et al, 2002;Shimodaira et al, 2010). Moreover, single-nucleotide polymorphisms in the HSD3B1 gene, the human ortholog of Hsd3b6, are associated with elevated systolic and diastolic blood pressure and plasma aldosterone activity (Rosmond et al, 2002;Shimodaira et al, 2010).…”
Section: (B) Circadian Regulation Of Gc Action Prior To Binding To Gmentioning
confidence: 99%
“…Cry1/2 −/− mice show elevated transcription and enhanced enzymatic activity of type VI 3β-hydroxyl-steroid dehydrogenase (Hsd3b6), which is expressed exclusively in aldosterone-producing cells under transcriptional control of the circadian clock. Moreover, single-nucleotide polymorphisms in the HSD3B1 gene, the human ortholog of Hsd3b6, are associated with elevated systolic and diastolic blood pressure and plasma aldosterone activity (Rosmond et al, 2002;Shimodaira et al, 2010). Moreover, single-nucleotide polymorphisms in the HSD3B1 gene, the human ortholog of Hsd3b6, are associated with elevated systolic and diastolic blood pressure and plasma aldosterone activity (Rosmond et al, 2002;Shimodaira et al, 2010).…”
Section: (B) Circadian Regulation Of Gc Action Prior To Binding To Gmentioning
confidence: 99%
“…In fact, recent association studies have suggested that specific haplotypes of EMILIN1 are useful genetic markers of essential hypertension in Japanese men and that the interaction of age and genotype variation of specific single nucleotide polymorphisms might increase the risk of hypertension in a northern Han Chinese population. 6,7 Here, we have addressed the question of the cellular context of Emilin-1 activity using a phenotype rescue approach by expressing the protein in either ECs or VSMCs or in all cells of the arterial wall of Emilin1 −/− mice. Our results indicate that Emilin-1 expression in VSMCs is specifically required for BP control and further clarify that the protein regulates the arteriolar myogenic response through TGF-β.…”
mentioning
confidence: 99%
“…Many candidate genes have been reported to be involved in essential hypertension susceptibility, including TSC, NEDD4L (Luo et al, 2009), CYP4F2 (Ward et al, 2008), EMILIN 1 (Shimodaira et al, 2010), ATP2B1 (Tabara et al, 2010), apelin-AGTRL1 system (Niu et al, 2010), and so on. Several studies suggest that TSC plays a major role in sodium and chloride re-absorption in the distal convoluted tubule, accounting for a significant proportion of the total renal sodium re-absorption (Plotkin et al, 1996;Matsuo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%